2019
DOI: 10.7554/elife.43654
|View full text |Cite
|
Sign up to set email alerts
|

Requirements for RNA polymerase II preinitiation complex formation in vivo

Abstract: Transcription by RNA polymerase II requires assembly of a preinitiation complex (PIC) composed of general transcription factors (GTFs) bound at the promoter. In vitro, some GTFs are essential for transcription, whereas others are not required under certain conditions. PICs are stable in the absence of nucleotide triphosphates, and subsets of GTFs can form partial PICs. By depleting individual GTFs in yeast cells, we show that all GTFs are essential for TBP binding and transcription, suggesting that partial PIC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
50
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(64 citation statements)
references
References 61 publications
(142 reference statements)
13
50
1
Order By: Relevance
“…At the same time, there is considerable overlap between the TBP/Taf ratios (and of other properties) between TATA+ and TATApromoters; the most parsimonious explanation is that either of at least two distinct mechanisms or pathways can operate at both types of promoters, but their relative efficiency differs depending on the presence of a consensus TATA element. This notion is consistent with the idea that the categorization of genes as SAGA-and TFIID-dominated reflects a continuum in terms of regulation, not a rigid dichotomy [4,5,34]. We also observed a greater increase in occupancy by Taf1 and Taf4 upon Kin28 depletion at TFIID-dominated than at SAGA-dominated promoters (Fig.…”
Section: Discussionsupporting
confidence: 91%
“…At the same time, there is considerable overlap between the TBP/Taf ratios (and of other properties) between TATA+ and TATApromoters; the most parsimonious explanation is that either of at least two distinct mechanisms or pathways can operate at both types of promoters, but their relative efficiency differs depending on the presence of a consensus TATA element. This notion is consistent with the idea that the categorization of genes as SAGA-and TFIID-dominated reflects a continuum in terms of regulation, not a rigid dichotomy [4,5,34]. We also observed a greater increase in occupancy by Taf1 and Taf4 upon Kin28 depletion at TFIID-dominated than at SAGA-dominated promoters (Fig.…”
Section: Discussionsupporting
confidence: 91%
“…These new results differ from our prior Pol II ChIP experiments that did not detect gene specific Taf requirements (Warfield et al, 2017). However, it was recently suggested that this may be due to background issues with Pol II ChIP data (e.g., stalled or paused Pols) and that Pol II ChIP is best used for quantitation of changes in highly expressed genes (Petrenko et al, 2019). This explanation is consistent with our new findings.…”
Section: Differences Between "Coactivator-redundant" Genes and "Saga-supporting
confidence: 67%
“…Yeast cellular transcription is dominated by a small number of exceptionally highly expressed 1 genes and it was proposed that highly expressed genes are biased for Taf-independent 2 expression (Petrenko et al, 2019). We do find that the coactivator-redundant genes, while 3 spread throughout the range of expressed genes, are enriched in the top 10% of transcribed 4 genes.…”
mentioning
confidence: 56%
See 2 more Smart Citations